Isolation and Lipid Decomposition Efficiency of Bacteria Isolated from Canteen Wastewater - มุขขันธ์, พรพิมล; อาษา, ปรารถนา; น้อยสำแดง, ภิรมย์ (Progress in Applied Science and Technology, 2017)
The aims of this research were to isolate the lipid degrading bacteria from canteen wastewater and to study the lipid hydrolysis efficiency of selected bacteria in the synthetic lipid wastewater. Twenty purified bacterial isolates obtained by randomly colonial selection were primarily tested for lipase enzyme production by using Tributyrin agar medium. As a result, nine of twenty isolates (9/20 isolates, 45%) which were isolates WA4, WA5, WA8, WA9, WA11, WA13, WA14, WA18 and WA19 could generate the clear zone; while the isolate WA5 gave the highest clear zone of 7.5 millimeters, indicating all nine isolates were lipolytic bacteria. Four of nine isolates (4/9, 44.44%) were gram positive with rod-shape, two of nine (2/9, 22.22%) isolate were gram positive with cocci-shape and three of nine (3/9, 33.33%) isolates were gram negative with rod-shape bacteria. The isolate WA5 was selected for testing the lipid hydrolysis efficiency. The result found that it could decompose the synthetic lipid wastewater containing plant lipid and animal lipid by decreasing the lipid concentration in average of 20.44% and 52.84%, respectively. While, the Bacillus subtilis laboratory strain could reduce the lipid concentration in average of 7.20% and 10.72%, respectively. It was indicated that the isolate WA5 which was isolated from lipid contaminated environment had higher hydrolysis efficiency than B. subtilis by 3-5 times.